2018
DOI: 10.1111/cod.13098
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary prevention of occupational skin diseases: Prevalence of allergic contact dermatitis and pattern of patch test results

Abstract: Background Allergic contact dermatitis (ACD) is one of the most common occupational skin diseases (OSDs). Its prevalence and the causative allergens differ between occupations. Objectives To evaluate the prevalence of ACD and the pattern of patch test results of patients taking part in a tertiary individual prevention programme (TIP) for OSD in Germany. Patients and Methods In a retrospective cohort study, the data of 3411 TIP patients patch tested between 2007 and 2016 were analysed. Results In 2687 (78.8%) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 61 publications
4
43
0
5
Order By: Relevance
“…Regarding the sites of occurrence, in agreement with previous studies, 3,8,51,59 we observed that OCD had a much higher proportion of hand involvement than non‐OCD (76.6% vs. 36.1%, OR 5.79; 95% CI 5.17–6.48), whereas leg and face dermatitis was rare. Among persons with OCD there were no significant differences regarding hand and leg localization between genders, whereas women had a significantly higher frequency of face dermatitis than men.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Regarding the sites of occurrence, in agreement with previous studies, 3,8,51,59 we observed that OCD had a much higher proportion of hand involvement than non‐OCD (76.6% vs. 36.1%, OR 5.79; 95% CI 5.17–6.48), whereas leg and face dermatitis was rare. Among persons with OCD there were no significant differences regarding hand and leg localization between genders, whereas women had a significantly higher frequency of face dermatitis than men.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the diagnosis, we find that ACD is predominant in our population (56.5% vs 43.5%) with a slightly higher proportion, as compared to ICD, among individuals with OCD (OR 1.14; 95%CI 1.04–1.26). Generally, ICD is the most common type of CD reported in literature, accounting for 60–80% of all CD, while ACD accounts for the remaining 20–40%, 6,41,51 but the proportion may vary widely across studies, depending on the occupations that prevail and the hazards to which people are exposed, the centers that report cases, and differences in the diagnostic criteria 4,5,52,53 . In comparison, a previous Italian study from Sertoli et al found that ACD clearly predominates over ICD (64,4% vs 34,6%, respectively) 14 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Awareness of workers is often underdeveloped, for instance, concerning contact with contaminated surfaces such as benches, clothing and tools [168]. Epoxy resin systems are known to cause face dermatitis [169] either via airborne contact or accidental exposure, e.g., in painters who are often sensitised to these (and to isothiazolinones which may also cause airborne ACD) [170].…”
Section: Plastic Monomers and Rubbermentioning
confidence: 99%